2021
DOI: 10.1001/jamaneurol.2020.5536
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Gender Minority Health in Neurology

Abstract: ittle is known about the neurologic health needs of sexual and gender minority (SGM) individuals (ie, those in the lesbian, gay, bisexual, transgender, and queer [LGBTQ+] spectrum). Understanding an individual's identity is essential for patientcentered communication, which improves patient satisfaction and reduces health disparities. SGM identity directly impacts a variety of neurologic conditions, including epilepsy, 1 dementia, 2 and stroke. 3,4 Neurologists receive little to no dedicated SGM health trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 76 publications
0
31
0
Order By: Relevance
“…Previous research has explored the potential impact of excluding non-English language literature and did not identify evidence of systemic bias based on this exclusion criteria. 16 As such, our observations raise the concern that sex-based neurological data are over-represented by three main regions and underrepresented by some of the most population dense regions in the world that may have unique biological and cultural influences on sex-based and gender-based research in neurology.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous research has explored the potential impact of excluding non-English language literature and did not identify evidence of systemic bias based on this exclusion criteria. 16 As such, our observations raise the concern that sex-based neurological data are over-represented by three main regions and underrepresented by some of the most population dense regions in the world that may have unique biological and cultural influences on sex-based and gender-based research in neurology.…”
Section: Discussionmentioning
confidence: 73%
“…Although our scoping review focused on binary terms of male and female, men and women, we recognise that sex and gender issues in the neurosciences reflect a spectrum, including transgender, intersex and non-binary identities as examples of the diversity that truly reflects the greater population. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Preventive care in this patient population is paramount because there are reports of depression, substance use, health care disparities including lower rates of cancer screening, higher incidence of certain cancers, and higher cancer mortality rates [ 86 – 88 ]. Providers should also manage their personal biases when caring for the LGBTQIA + as the literature reports that the patients may conceal their sexual orientation and gender identity for fear of suboptimal quality of care [ 85 , 89 – 91 ]. For patients using gender-affirming hormone therapy (GAHT) such as exogenous feminizing hormones or masculinizing hormones, their unique needs cannot be ignored, highlighting the importance of health care providers being aware so that proper care is delivered and timely referrals to specialists made [ 13 , 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Despite the community's diversity in racial, ethnic, socioeconomic, and cultural backgrounds, they face common adversities which can translate into poor health outcomes, 3 although to date most research has disproportionately focused on psychiatric conditions and HIV. 4 For example, stroke is the leading cause of disability and fifth leading cause of death in the United States 5 ; however, little is known about stroke in SGM people. 6 Previous studies have identified increased cardiovascular risk among SGM people, 7 , 8 as well as unique and disproportionate stroke risk factors in transgender people, 9 although none have compared SGM and non-SGM people with stroke to assess for differences in clinical outcomes.…”
mentioning
confidence: 99%